Pondok Pesantren Mojosari dan Kontribusinya terhadap Taraf Pendidikan Masyarakat Kabupaten Nganjuk - Silvia, Faiqotus; Said, Imam Ghazali; Hajar, Imam Ibnu (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2022)
The article discusses (1). General Description of the Condition of the Ngepeh Village Community and the Development of Islam of the Nganjuk Region, (2). History of Development in the Establishment of the Nahdlatul Ulama Educational Foundation Pondok Pesantren Mojosari, (3). The Contribution of the Nahdlatul Ulama Education Foundation of Mojosari Islamic Boarding School to the Ngepeh Village Community, Loceret Distrct, Nganjuk Regency. Using the historical method, the four stages are : Heuristics, Verification, Interpretation, and Historiography. Using a Sociological Historical Approach to analyze the Pondok Pesantren Mojosari influence on education in Ngepeh Village. Using Ibnu Khaldun’s Historical Motion Theory, K.H. Ali Imran as a historical driving figure for spreading Islam in Ngepeh Village and Emile Durkheim’s Structural Functional Theory described Pondok Pesantren Mojosari as a place for children’s education. The conclusions is : (1). K.H. Ali Imran spread Islam with the establishment of the Pondok Pesantren Mojosari (1720 AD), (2). Pondok Pesantren Mojosari formed the Nahdlatul Ulama Education Foundation by K.H. Ahmad Basthomi Zaini provided formal and informal education (1995 AD), (3). The Nahdlatul Ulama Education Foundation Pondok Pesantren Mojosari contributes to the Ngepeh Village Community with the existence of TQ Al-Furqan (1995 AD) and the Mojosari Institute of Technology (2021 AD).